Formulation and Evaluation of Miconazole Nitrate Solid Dispersions for Dissolution Rate Enhancement - Janjale, Minakshi V (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Solid Dispersions of miconazole nitrate (MN), with a water soluble polymer (PVP) and a super disintegrant namely, crospovidone (CP), were prepared by common solvent and solvent evaporation methods employing methanol as solvent. Solid Dispersions prepared were evaluated for dissolution rate and dissolution efficiency in comparison to the corresponding pure drug miconazole nitrate. Solid dispersions of miconazole nitrate showed a marked enhancement in dissolution rate and dissolution efficiency. The order of increasing dissolution rate was observed with increase in crospovidone ratio. At 1:4 ratio of miconazole nitrate?óÔé¼?ÉCP a 2.26 fold increase in the dissolution rate of miconazole nitrate was observed. The solid dispersions in combined carriers gave much higher rates of dissolution than super disintegrants alone. MN-CP?óÔé¼?ÉPVP solid dispersion gave a 3.47 fold increase in the dissolution rate of miconazole nitrate. Superdisintegrants alone or in combination with PVP could be used to enhance the dissolution rate of poorly soluble drug miconazole nitrate.